It takes a township - McNiff, J (South African Journal of Higher Education, 2011)
In this article I argue for higher education practitioners to take focused action to contribute to transforming their societies into open and democratically negotiated forms of living, and why they should do so. The need is especially urgent in South Africa, whose earlier revolutionary spirit led to massive social change. The kind of social transformation I have in mind is where all people are seen as equal in all domains, including capacity to do research and generate theory; especially significant given that social evolution is linked with knowledge creation. Drawing on personal stories of experience, I make a case for universities to create innovative professional pathways that will encourage the fulfilment of intellectual potential by all practitioners, not only elites, taking as a main criterion for judging the quality of practice whether one has contributed to the wellbeing of a township, however this may be construed.